The Fruit-Color Polymorphism in Gaultheria Mucronata (L.F.) Hook. & Arn. Does Not Affect Pre-Dispersive Germination [el Polimorfismo en el Color de Frutos de Gaultheria Mucronata (L.F.) Hook. & Arn. No Afecta Su Germinación Predispersiva] - Castro-Morales, S (Universidad de Concepcion, 2022)
The germinative dynamics of Gaultheria mucronata (L.f.) Hook. & Arn. seeds from fruits of different colors were compared. Seeds from white, pink and dark-pink fruits were subjected to germination trials, evaluating the final germination percentage, accumulated germination percentage and the mean germination period (T50). The results did not show statistically significant differences between the treatments, implying that the fruit color polymorphism does not show differences in the germinative behavior analyzed here. © 2022 The author(s).